Physics and the canalization of morphogenesis: a grand challenge in organismal biology - von Dassow, Michelangelo (2011)
Morphogenesis takes place in a background of organism-to-organism and environmental variation. Therefore, a fundamental question in the study of morphogenesis is how the mechanical processes of tissue movement and deformation are affected by that variability, and in turn, how the mechanics of the system modulates phenotypic variation. We highlight a few key factors, including environmental temperature, embryo size, and environmental chemistry that might perturb the mechanics of morphogenesis in natural populations. Then we discuss several ways in which mechanics – including feedback from mechanical cues – might influence intra-specific variation in morphogenesis. To understand morphogenesis it will be necessary to consider whole-organism, environment, and evolutionary scales because these larger scales present the challenges that developmental mechanisms have evolved to cope with. Studying the variation organisms express and the variation organisms experience will aid in deciphering the causes of birth defects.